Ecoprint short course with ecopounding techniques for the international community - Eka Nuryanto Budisusila; Agus Adhi Nugroho; Wiwiek Fatmawati; Rieska Ernawati (Universitas Muhammadiyah Magelang, 2023)
Fabric coloring and motif techniques using the ecoprint method are starting to be widely applied, although not many people know how to apply it. One ecoprint method is the ecopounding technique. The community service aims to introduce the ecoprint technique using the ecopounding method to the wider community, both on a national and international scale. This training was carried out using online zoom meeting media which was attended by 70 participants from 7 countries, namely the Philippines, Bangladesh, Malaysia, Mongolia, Afghanistan, Kazakhstan and Indonesia. This training succeeded in adding knowledge and improving participants' skills in making fabric motifs using the ecopounding method. Apart from that, the evaluation results showed that 97% of participants expressed satisfaction and enjoyment with this short course.